2014
DOI: 10.1093/scan/nsu090
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of informational cascades: brain mechanisms of social influence on belief updating

Abstract: Informational cascades can occur when rationally acting individuals decide independently of their private information and follow the decisions of preceding decision-makers. In the process of updating beliefs, differences in the weighting of private and publicly available social information may modulate the probability that a cascade starts in a decisive way. By using functional magnetic resonance imaging, we examined neural activity while participants updated their beliefs based on the decisions of two fictiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 44 publications
2
48
1
Order By: Relevance
“…How human choice behavior is influenced by the confluence of private and social information has been an active research topic in the fields of psychology and social neuroscience. Aided by formal decision theory and neuroimaging techniques, it has been shown that brain regions such as cingulate cortex (posterior cingulate cortex and dACC) and dmPFC play a critical role in conforming to social influences (Burke, Tobler, Schultz, & Baddeley, ; De Martino et al, ; Huber, Klucharev, & Rieskamp, ; Klucharev et al, ; Klucharev et al, ; Park, Goïame, O'Connor, & Dreher, ; Wu et al, ; Zaki et al, ). However, whether and how human can dynamically adjust their behavior based on the informational content remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…How human choice behavior is influenced by the confluence of private and social information has been an active research topic in the fields of psychology and social neuroscience. Aided by formal decision theory and neuroimaging techniques, it has been shown that brain regions such as cingulate cortex (posterior cingulate cortex and dACC) and dmPFC play a critical role in conforming to social influences (Burke, Tobler, Schultz, & Baddeley, ; De Martino et al, ; Huber, Klucharev, & Rieskamp, ; Klucharev et al, ; Klucharev et al, ; Park, Goïame, O'Connor, & Dreher, ; Wu et al, ; Zaki et al, ). However, whether and how human can dynamically adjust their behavior based on the informational content remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to perceptual decision-making, this joint decision does not necessarily lead to an increased accuracy for both players and, in fact, a player with high accuracy will often suffer a decrement in joint accuracy. Consequently, in individual decisionmaking contexts where there is provision of additional social information, participants overproportionally discount social information depending on their own accuracy [41] and individual predisposition [42][43][44].…”
Section: Combining Social and Individual Informationmentioning
confidence: 99%
“…There is a growing interest in decision neuroscience in studying the effect of prior expectation on behavioral performance and the underlying neural mechanisms, ranging from perceptual decision making (Forstmann et al, 2010;Rahnev et al, 2011;Mulder et al, 2012;Kok et al, 2013), reinforcement learning (Li et al, 2011), belief updating in financial decision making in the presence of social information (Huber et al, 2014), and in trust games (Fouragnan et al, 2013). Prior expectations in most studies were manipulated by varying the reliability of cues that predicts the upcoming stimulus (Forstmann et al, 2010;Li et al, 2011;Rahnev et al, 2011;Mulder et al, 2012;Kok et al, 2013) or simply the presence or absence of prior information (Fouragnan et al, 2013).…”
Section: Integration Of Prior and Likelihood Informationmentioning
confidence: 99%
“…In a financial decision task, Huber et al, (2014) found that frontoparietal regions including the inferior parietal cortex and the DLPFC update beliefs about option value in the presence of social information. To summarize, a growing body of work has begun to reveal the neural systems involved in representing prior expectations and the compu- Figure 5.…”
Section: Integration Of Prior and Likelihood Informationmentioning
confidence: 99%